2021
DOI: 10.1039/d1ce00334h
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of carboxylated pillar[5]arene and strontium(ii) into supramolecular coordination complexes of different nuclearities

Abstract: We show that the nuclearity of the 2-D coordination polymers of carboxylated pillar[5]arene with Sr(II) cations can be varied with the aid of 1,10-phenanthroline as a coligand. In the absence...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…This HB with a very short O–H···O distance of 2.47 Å evidences the carboxylic–carboxylate COOH···COO – supramolecular synthon and confirms the deprotonation of some of the carboxylic substituents of CPA5 . Taking into account that we observed such carboxyl–carboxylate HBs with O–H···O distances shorter than 2.50 Å also in the CPA5 –viologen inclusion complexes and coordination complexes with strontium, it can be stated that they are characteristic features of the solid-state CPA5 assembly and are realized also in the presence of competing heterosyntons (such as amidinium–carboxylate). Hydrogen bonding between pentamidine and CPA5 gives rise to a chainlike assembly via amidinium–carboxylate interactions in which PTM @ CPA5 supramolecules are shifted “up and down” in relation to each other (Figure ); in addition, adjacent chains are stapled by short carboxylic–carboxylate HBs between CPA5 molecules.…”
Section: Resultsmentioning
confidence: 55%
“…This HB with a very short O–H···O distance of 2.47 Å evidences the carboxylic–carboxylate COOH···COO – supramolecular synthon and confirms the deprotonation of some of the carboxylic substituents of CPA5 . Taking into account that we observed such carboxyl–carboxylate HBs with O–H···O distances shorter than 2.50 Å also in the CPA5 –viologen inclusion complexes and coordination complexes with strontium, it can be stated that they are characteristic features of the solid-state CPA5 assembly and are realized also in the presence of competing heterosyntons (such as amidinium–carboxylate). Hydrogen bonding between pentamidine and CPA5 gives rise to a chainlike assembly via amidinium–carboxylate interactions in which PTM @ CPA5 supramolecules are shifted “up and down” in relation to each other (Figure ); in addition, adjacent chains are stapled by short carboxylic–carboxylate HBs between CPA5 molecules.…”
Section: Resultsmentioning
confidence: 55%
“…17 In our further solid state structural studies CPA5 has shown its ability to complex viologen derivatives 18 and to form coordination polymers with alkali-earth cations. 19 Recently, we have demonstrated the rich host−guest chemistry of CPA5pentamidine crystal complexes highlighting the role of amidinium-carboxylate hydrogen bonding and cavity inclusion. 20 Despite the thriving interest in the aqueous complexation properties of larger pillar[n]arenes, 21,22 their solid state supramolecular chemistry has remained a mystery.…”
mentioning
confidence: 99%
“…Satisfying our scientific curiosity with a view to design and construct novel supramolecular structures, we managed to crystallize carboxylated pillar[5]­arene ( CPA5 ) in the form of inclusion complexes with ethanol and the anesthetic drug tetracaine in 2015 . In our further solid state structural studies CPA5 has shown its ability to complex viologen derivatives and to form coordination polymers with alkali-earth cations . Recently, we have demonstrated the rich host–guest chemistry of CPA5 -pentamidine crystal complexes highlighting the role of amidinium-carboxylate hydrogen bonding and cavity inclusion …”
mentioning
confidence: 99%
“…We managed for the first time to trap in the crystal state both pillar[5]­arene and pillar[6]­arene in the form of host–guest complexes. We have shown that carboxylated pillar[5]­arene ( CPA5 ) forms inclusion and exclusion complexes with electron-deficient viologen guests and coordination complexes with metal cations . In the current study, we have chosen two biguanide cationic guests, alexidine ( ALEX ) and phenformin ( PFM ), as partner species to crystallize with CPA5 , as shown in Figure .…”
Section: Introductionmentioning
confidence: 99%
“…We have shown that carboxylated pillar [5]arene (CPA5) forms inclusion and exclusion complexes with electron-deficient viologen guests 16 and coordination complexes with metal cations. 17 In the current study, we have chosen two biguanide cationic guests, alexidine (ALEX) and phenformin (PFM), as partner species to crystallize with CPA5, as shown in Figure 1. Biguanides are important pharmaceutical molecules of the rich palette of activity; they have been used inter alia as antidiabetic, antiseptic, or antimalaria drugs.…”
Section: ■ Introductionmentioning
confidence: 99%